Competence evaluation of COSAC flight spare model mass spectrometer: In preparation of arrival of Philae lander on comet 67P/Churyumov–Gerasimenko. (February 2015) - Giri, Chaitanya; Goesmann, Fred; Steele, Andrew; Gautier, Thomas; Steininger, Harald; Krüger, Harald; Meierhenrich, Uwe J.
Abstract: The Cometary Sampling and Composition (COSAC) experiment onboard the Philae lander is a combined Gas Chromatograph–Mass Spectrometer targeted to determine the organic composition of the nucleus of comet 67P/Churyumov–Gerasimenko. The COSAC flight-model mass spectrometer (FM-MS) was scheduled to sample volatile organic species from 67P׳s coma prior to Philae׳s detachment from the Rosetta orbiter in November 2014. It was again scheduled to sample subsequent to Philae׳s touchdown but prior to drilling operations, thereby retrieving measurements of volatiles from the surface of an unperturbed nucleus. This article evaluates the competence of COSAC mass spectrometers in identifying volatile organic species in both cometary and laboratory-simulated environments. The evaluation was conducted on an operationally optimized COSAC flight spare model mass spectrometer (FS-MS) maintained in ultra-high vacuum. The FS-MS obtained analytical measurements by "sniffing" several organic molecule mixtures of diverse chemical functional groups and molecules with broader molecular masses introduced into the vacuum vessel housing the instrument. The results demonstrate that COSAC produces mass fragmentation patterns of organic species similar to those in calibration standard mass spectra; it is able to identify various organic species within mixtures present at low concentrations (100 ppm); and it can identify fragmentation patterns of non-introduced unknown species and those with high molecular masses within organic mixtures. These observations successfully substantiate the potential of the FM-MS to make qualitative measurements of organic species both in the rarefied environment of the coma and in the relatively enriched nucleus surface. Highlights: This is the first comparative analyses of COSAC data with measurement standards. COSAC can identify organic species present at very low concentrations. It can identify mass fragmentation patterns of unknown species. It can identify mass fragmentation patterns of high molecular mass species. COSAC is competent to detect organic volatile species native to comet 67P.